Pengembangan Animasi Interaktif Sebagai Media Pembelajaran Kebudayaan Indonesia Dengan Model ADDIE - Rosmiati, Mia; Sulistiyah, Sulistiyah; Farabi, Nur Ali; Susanti, Susanti (MULTINETICS, 2023)
Learning media that only rely on writing tools such as books, paper, pencils or pens in the teaching and learning process cause communication errors between parents, teachers and children or students. In this case the learning media must be more creative in applying learning methods to increase interest in learning in children. With this interactive animation application learning to know Indonesian culture, it is hoped that it can provide benefits for our children. Indonesian culture interactive animation was developed using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) software development model. The learning media presented is of course learning while playing with the aim of fostering interest in learning and introducing information technology to children, especially regarding Indonesian arts and culture. Based on the calculation results of the questionnaire, it was obtained that 95.5% answered yes and 4.5% answered no. So that it results that students can easily use this application, become more interested in learning interactive animation to know Indonesian art and culture and can be used as a tool that can help students learn to recognize interactive animation to know Indonesian art and culture so that learning is not boring.